Inovasi Festival Bandung Innovation Contest And Coaching Clinic ICONIC Dalam Menciptakan Dampak Ekonomi Positif Melalui Pemberdayaan Lingkungan - Diva Syafilla Bunga Dinanthi; Raisa Rafifiti Choerunnisa (RJABM (Research Journal of Accounting and Business Management), 2025)
The city of Bandung faces serious challenges in environmental management, especially after the Sarimukti landfill fire, which impacted the local economy, particularly MSMEs. The Bandung City Government, through Bapperida, collaborates with communities, MSME actors, and society as collaborative agents. This research analyzes how the Bandung ICONIC Festival functions as a collaborative innovation that connects environmental issues with economic growth through empowerment. A literature study with a descriptive-qualitative approach uses the cross-sector collaboration theory from Bryson, Crosby, and Stone (2006) as an analytical framework. The ICONIC Festival successfully created an environmentally-based creative economy ecosystem that strengthens the role of MSMEs and enhances public literacy on sustainability issues. Recommendations are provided for integrating thematic environmental approaches into urban development policies.